Role of Ruthenium Oxidation States in Ligand-to-Ligand Charge Transfer Processes - Ramirez, Cristina Lujan (2012)
We describe in this paper the properties of [RuII/III(bpy)2ClL]+1/+2 and [RuII/III(bpy)2L2]+2/+3. L = ditolyl-3-pyridylamine (dt3pya) is a redox active ligand related to triarylamines, which is very similar to 3-aminopyridine except for the reversible redox behavior. The monosubstituted complex shows a metal-to-ligand charge-transfer (MLCT) at 502 nm, and reversible waves in acetonitrile at E0(RuIII/II) = 1.07 V, E0(L+/0) = 1.46 V (NHE). The disubstituted complex shows an MLCT at 461 nm, a photorelease of dt3pya with quantum yield of 0.11 at 473 nm, and two reversible one-electron overlapped waves at 1.39 V associated with one of the ligands (1.37 V) and RuIII/II (1.41 V). Further oxidation of the second ligand at 1.80 V forms a 2,2′-bipiridine derivative, in an irreversible reaction similar to dimerization of triphenylamine to yield tetraphenylbenzidine. In the dioxidized state, the spectroelectrochemistry of the disubstituted complex shows a ligand-to-ligand charge transfer at 1425 nm, with a transition moment of 1.25 Å and an effective two-state coupling of 1200 cm–1. No charge transfer between ligands was observed when Ru was in a 2+ oxidation state. We propose that a superexchange process would be involved in ligand–metal–ligand charge transfer, when ligands and metals are engaged in complementary π interactions, as in metal–ligand–metal complexes. Best orbital matching occurs when metallic donor fragments are combined with acceptor ligands and vice versa. In our case, RuIII bridge (an acceptor) and two dt3pya (donors, one of them being oxidized) made the complex a Robin–Day Class II system, while the RuII bridge (a donor, reduced) was not able to couple two dt3pya (also donors, one oxidized).